2nd International Congress on Acoustical and Vibratory Surveillance Methods and Diagnostic Techniques - Editorial Board Archives of Acoustics (Archives of Acoustics, 2025)
The Congress is hosted by a research centre (D.E.R.) of Electricité de France (E.D.F.)